Preparation method of bio-based membrane with efficient waterproof and moisture permeable performance

PU nanofiber membranes are prepared through electrospinning technology, and silica particles are grafted on their surface to form a waterproof and permeable membrane with a multi-layer pore structure, which solves the problem that existing waterproof and permeable membranes are difficult to meet the waterproof and moisture permeable properties at the same time, and achieves efficient and environmentally friendly bio-based membrane preparation.

CN119531124AActive Publication Date: 2025-02-28ANTA (CHINA) CO LTD

Patent Information

Application Number
CN202411872140.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-02-28
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing waterproof and moisture-permeable films are difficult to meet both waterproof and moisture-permeable properties in practical applications, and traditional preparation methods use harmful organic solvents and non-degradable petroleum-based raw materials to affect the environment and human health.

Method used

PU nanofiber membranes were prepared by electrospinning technology, and silica particles were grafted on their surface by hydrothermal assisted sol-gel process to form a waterproof and permeable membrane with a multi-layered pore structure, and an environmentally friendly solvent was used to replace traditional solvents.

Benefits of technology

It realizes the efficient waterproof and moisture permeability of the bio-based membrane, improves the durability and breathable comfort of the membrane, and reduces the harm to the environment and human health, and meets environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005196020250000071
    Figure BDA0005196020250000071
Patent Text Reader

Abstract

The invention provides a preparation method of a bio-based membrane with efficient waterproof and moisture permeable performance, which comprises the following steps: a) mixing polyurethane, a polymer and a mixed solvent to obtain a mixed solution; the polymer is selected from one or more of PVA (Polyvinyl Alcohol), PVA-co-PE (Polyvinyl Alcohol-co-Polyethylene) and chitosan; b) stirring the mixed solution, standing and defoaming; c) performing electrostatic spinning on the obtained spinning solution; d) grafting silicon dioxide particles on the surface of the obtained PU nanofiber membrane by adopting a hydrothermal assisted sol-gel process, carrying out heat treatment, soaking, taking out, and continuously carrying out heat treatment; e) soaking the obtained PU nanofiber membrane grafted with the SiO2 particles on the surface in an ethanol solution containing tetraethoxysilane, taking out and carrying out heat treatment; and f) drying and cooling the obtained waterproof permeable membrane with the multi-layer pore structure to obtain the bio-based membrane with efficient waterproof and moisture-permeable properties. The bio-based membrane prepared by the method has efficient waterproof and moisture permeable properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bio-based membranes, and in particular relates to a method for preparing a bio-based membrane with high-efficiency waterproof and moisture-permeable properties. Background Art

[0002] With the improvement of environmental awareness, the preparation technology of bio-based materials has received more and more attention. Bio-based materials refer to materials prepared by chemical, physical or biological methods using biomass as raw materials, which have the advantages of being renewable and degradable. Among them, electrospinning technology is a new type of nanofiber preparation technology that can prepare nanofiber membranes with high specific surface area and high porosity, which are widely used in filtration, protection, biomedicine and other fields. Waterproof and breathable membranes are an important type of functional membrane, mainly used in outdoor clothing, medical equipment, etc., which require good waterproof performance while ensuring a certain degree of breathability to maintain human comfort.

[0003] Existing waterproof and breathable membranes are mainly prepared by microporous membrane technology. By controlling the microporous structure of the membrane, a balance between waterproofness and breathability can be achieved. However, there are still some problems with existing waterproof and breathable membranes in practical applications. First of all, it is often difficult to meet the waterproof and breathable properties of microporous membranes at the same time. Either the waterproof performance is good but the breathable performance is poor, or the breathable performance is good but the waterproof performance is poor. Traditional methods for preparing waterproof coatings often require the use of organic solvents, such as DMF (dimethylformamide). These solvents are not only harmful to the environment, but also have a certain impact on human health. In addition, most of the existing waterproof and breathable membranes use petroleum-based raw materials, which are not environmentally friendly and non-degradable, causing pressure on the environment. Summary of the invention

[0004] In view of this, an object of the present invention is to provide a method for preparing a bio-based membrane with high-efficiency waterproof and moisture-permeable properties, wherein the bio-based membrane prepared by the method has excellent air permeability and waterproofness.

[0005] The present invention provides a method for preparing a bio-based membrane with high-efficiency waterproof and moisture permeability, comprising the following steps:

[0006] a) mixing polyurethane, polymer and mixed solvent to obtain a mixed solution; the polymer is selected from one or more of PVA, PVA-co-PE and chitosan;

[0007] b) stirring the mixed solution, allowing it to stand for degassing to obtain a spinning solution;

[0008] c) electrospinning the spinning solution to obtain a PU nanofiber membrane;

[0009] d) using a hydrothermal assisted sol-gel process to graft silica particles on the surface of the PU nanofiber membrane, heat-treating, soaking, taking out and continuing heat-treating to obtain a PU nanofiber membrane with SiO2 particles grafted on the surface;

[0010] e) soaking the PU nanofiber membrane with SiO2 particles grafted on the surface in an ethanol solution containing ethyl orthosilicate, taking it out and performing heat treatment to obtain a waterproof and permeable membrane with a multi-level pore structure;

[0011] f) drying and cooling the waterproof and permeable membrane with a multi-level pore structure to obtain a bio-based membrane with high-efficiency waterproof and moisture permeability.

[0012] The present invention spins a mixed solution of PU and PVA or PVA-co-PE or chitosan, and grafts silicon dioxide (SiO2) particles on the surface of PU nanofibers to form a wear-resistant waterproof coating, so that the prepared waterproof and breathable membrane has excellent waterproof performance, can effectively prevent water intrusion, and has improved durability compared with traditional coatings.

[0013] In step a) of the present invention, the mass ratio of polyurethane (PU) and polymer is 1:0.8-1.2; the mixed solvent is a mixture of water, ethanol and isopropyl ketone (or acetone) in a mass ratio of 2:0.8-1.2:0.8-1.2; in a specific embodiment, the mixed solvent is a mixture of water, ethanol and acetone in a mass ratio of 2:1:1. In a specific embodiment, the mass ratio of PU and PVA is 1:1; the mass ratio of PU and PVA-co-PE is 1:1; the mass ratio of PU and chitosan is 1:1. The mixed solvent is water, ethanol and acetone in a mass ratio of 2:1:1. The mass ratio of polyurethane and polymer to the mixed solvent is 1:8.5-9.5, preferably 1:9. The mixed solution prepared by the present invention has good hydrophilicity and improves the moisture permeability effect. At the same time, the hydroxyl groups in PU, PVA and chitosan provide more reaction sites, which are easy to react with the waterproof coating.

[0014] The number average molecular weight of the polyurethane in step a) of the present invention is 75000-85000; the number average molecular weight of PVA is 9500-11000; the number average molecular weight of PVA-co-PE is 20000-77000; the number average molecular weight of chitosan is 50000-90000. In a specific embodiment, the number average molecular weight of the PU is 80000, the number average molecular weight of PVA is 10000, the number average molecular weight of PVA-co-PE is 20000, and the number average molecular weight of chitosan is 50000. The present invention uses bio-based raw materials to prepare a waterproof and breathable bio-based membrane, which has the advantages of being renewable and degradable. It uses environmentally friendly solvents instead of DMF solvents, meets environmental protection requirements, and reduces pressure on the environment and potential harm to human health.

[0015] In step b) of the present invention, the stirring temperature is 55-65°C for 1.5-2.5 hours, and the standing and degassing time is 11-13 hours. In a specific embodiment, the stirring temperature is 60°C for 2 hours, and the standing and degassing time is 12 hours.

[0016] The spinning solution is electrospun to obtain a PU nanofiber membrane. The present invention can obtain a nanofiber membrane with high porosity through the electrospinning process, thereby improving the waterproof performance and moisture permeability of the membrane. The voltage of the electrospinning in step c) of the present invention is 20 to 30 KV, and the receiving distance is 14.5 to 15.5 cm. The humidity of the electrospinning is 20 to 80%. In a specific embodiment, the voltage of the electrospinning is 20 KV, and the receiving distance is 15 cm.

[0017] The present invention adopts a hydrothermal assisted sol-gel process to graft silica particles on the surface of the PU nanofiber membrane, heat treat, soak, and continue heat treatment after taking out to obtain a PU nanofiber membrane with SiO2 particles grafted on the surface. The temperature of the heat treatment in step d) of the present invention is 85-95°C, and the time is 30-60min; in a specific embodiment, the temperature of the heat treatment is 90°C, and the time is 30min. The soaking liquid used for soaking in step d) of the present invention includes a diisocyanate, a silane coupling agent and ethanol in a mass ratio of 1:1:2; the diisocyanate is selected from toluene diisocyanate or diphenylmethane diisocyanate (MDI); the silane coupling agent is selected from KH-550 or LT-560; the soaking time is 24h. After soaking, take out and continue heat treatment, the temperature of continuing heat treatment is 55-65°C, and the time is 30-60min; in a specific embodiment, the temperature of continuing heat treatment is 60°C, and the time is 30min.

[0018] The present invention adopts a hydrothermal assisted sol-gel process to graft silicon dioxide (SiO2) particles on the surface of PU nanofibers, which can not only make the fiber membrane obtain a rough surface, but also reduce the fiber surface energy, further improving the waterproof performance of the PU nanofiber membrane. At the same time, it has good wear resistance, and can make the waterproof and breathable membrane still maintain good waterproof performance after multiple washings, thereby extending its service life.

[0019] The PU nanofiber membrane with SiO2 particles grafted on the surface is immersed in an ethanol solution containing ethyl orthosilicate, and then heat-treated after being taken out to obtain a waterproof and breathable membrane with a multi-level pore structure. The waterproof and breathable membrane with a multi-level pore structure formed by the present invention can make the pores decrease from the inside to the outside, and use the siphon effect to make the internal sweat easy to discharge and the external water difficult to enter, thereby improving the breathability, comfort and waterproof performance of the waterproof and breathable membrane. The temperature of the heat treatment after taking out in step e) of the present invention is 55-65°C and the time is 30-60min.

[0020] The drying in step f) of the present invention is vacuum drying or oven drying; the vacuum drying temperature is 55-65° C. and the time is 11-13 hours; the oven drying temperature is 75-85° C. and the time is 1-2 hours.

[0021] The cooling temperature in step f) of the present invention is 15-25° C., and the cooling time is 20-40 min. In a specific embodiment, the cooling temperature is 20° C., and the cooling time is 30 min.

[0022] The above-mentioned preparation process provided by the present invention adopts environmentally friendly solvents, such as a mixture of water, ethanol, and isopropanol, to reduce the use of organic solvents, reduce environmental pollution and the impact on human health. The preparation process saves energy and resources, and conforms to the concept of green development, such as adopting high-efficiency spinning equipment and energy-saving drying equipment, as well as reasonable production process design, to reduce energy consumption and waste.

[0023] The bio-based membrane with high-efficiency waterproof and moisture-permeable performance provided by the present invention is mainly used in outdoor jackets, which can provide good waterproof performance while ensuring a certain degree of moisture permeability, maintaining human comfort, and improving the safety and comfort of outdoor activities.

[0024] The present invention provides a method for preparing a bio-based membrane with high-efficiency waterproof and breathable performance, comprising the following steps: a) mixing polyurethane, a polymer and a mixed solvent to obtain a mixed solution; the polymer is selected from one or more of PVA, PVA-co-PE and chitosan; b) stirring the mixed solution, standing and degassing to obtain a spinning solution; c) electrospinning the spinning solution to obtain a PU nanofiber membrane; d) using a hydrothermal assisted sol-gel process to graft silica particles on the surface of the PU nanofiber membrane, heat-treating, soaking, and continuing heat-treating after taking out to obtain a PU nanofiber membrane with SiO2 particles grafted on the surface; e) soaking the PU nanofiber membrane with SiO2 particles grafted on the surface in an ethanol solution containing ethyl orthosilicate, taking out and heat-treating to obtain a waterproof and breathable membrane with a multi-level pore structure; f) drying the waterproof and breathable membrane with a multi-level pore structure, cooling, and obtaining a bio-based membrane with high-efficiency waterproof and breathable performance. The bio-based membrane prepared by the above method has high-efficiency waterproof and breathable performance. DETAILED DESCRIPTION

[0025] In order to further illustrate the present invention, the preparation method of a bio-based membrane with high-efficiency waterproof and moisture-permeable properties provided by the present invention is described in detail below in combination with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0026] In the following examples, the molecular weight of PU is 80,000, the molecular weight of PVA is 10,000, the molecular weight of PVA-co-PE is 20,000, and the molecular weight of chitosan is 50,000.

[0027] Example 1

[0028] Step a): Add a mixture of PU and PVA in a mass ratio of 1:1 into a mixed solvent, stir until completely dissolved, and obtain a mixed solution; wherein the mass ratio of the mixture to the mixed solvent is 1:9. The number average molecular weight of PU is 80,000, and the number average molecular weight of PVA is 10,000. The mixed solvent is prepared by mixing water, ethanol and acetone in a mass ratio of 2:1:1.

[0029] Step b): The mixed solution was stirred at 60° C. for 2 hours, and then allowed to stand at room temperature for degassing for 12 hours to obtain a spinning solution.

[0030] Step c): electrospin the spinning solution for 4 hours at a voltage of 20 kV and a receiving distance of 15 cm, changing the spinning humidity every hour to 20%, 40%, 60%, and 80%, respectively, to obtain a PU nanofiber membrane with a multi-level pore structure.

[0031] Step d): The obtained PU nanofiber membrane is heat-treated at 90°C for 30 minutes, then immersed in an ethanol solution containing diphenylmethane diisocyanate (MDI) and silane coupling agent KH-550 for 24 hours, and then heat-treated at 60°C for 30 minutes to obtain a PU nanofiber membrane with SiO2 particles grafted on the surface. The concentration of the silane coupling agent KH-550 is 5wt%, and the concentration of diphenylmethane diisocyanate is 10wt%.

[0032] Step e): Soak the PU nanofiber membrane with SiO2 particles grafted on the surface in an ethanol solution containing tetraethyl orthosilicate for 24 hours, take it out and heat-treat it at 60° C. for 30 minutes to obtain a waterproof and breathable membrane with a multi-level pore structure, wherein the concentration of tetraethyl orthosilicate is 5wt%.

[0033] Step f): vacuum drying the obtained waterproof and breathable membrane at 60° C. for 12 hours, cooling the dried waterproof and breathable membrane at a temperature of 20° C. for 30 minutes, and obtaining a bio-based membrane with high-efficiency waterproof and breathable properties.

[0034] Example 2

[0035] Step a): Add a mixture of PU and PVA-co-PE in a mass ratio of 1:1 into a mixed solvent, stir until completely dissolved, and obtain a mixed solution; wherein the mass ratio of the mixture to the mixed solvent is 1:9. The number average molecular weight of PU is 80,000, and the number average molecular weight of PVA-co-PE is 20,000. The mixed solvent is prepared by mixing water, ethanol and acetone in a mass ratio of 2:1:1.

[0036] Step b): The mixed solution was stirred at 60° C. for 2 hours, and then allowed to stand at room temperature for degassing for 12 hours to obtain a spinning solution.

[0037] Step c): electrospin the spinning solution for 4 hours at a voltage of 20 kV and a receiving distance of 15 cm, changing the spinning humidity every hour to 20%, 40%, 60%, and 80%, respectively, to obtain a PU nanofiber membrane with a multi-level pore structure.

[0038] Step d): The obtained PU nanofiber membrane is heat-treated at 90°C for 60 minutes, then immersed in an ethanol solution containing diphenylmethane diisocyanate (MDI) and silane coupling agent KH-550 for 24 hours, and then heat-treated at 60°C for 60 minutes to obtain a PU nanofiber membrane with surface grafted SiO2 particles. The concentration of the silane coupling agent KH-550 is 5wt%, and the concentration of diphenylmethane diisocyanate is 10wt%.

[0039] Step e): Soak the PU nanofiber membrane with SiO2 particles grafted on the surface in an ethanol solution containing tetraethyl orthosilicate for 24 hours, take it out and heat-treat it at 60° C. for 60 minutes to obtain a waterproof and breathable membrane with a multi-level pore structure, wherein the concentration of tetraethyl orthosilicate is 5wt%.

[0040] Step f): drying the obtained waterproof and breathable membrane at 80° C. for 1 hour, cooling the dried waterproof and breathable membrane at a temperature of 20° C. for 30 minutes, and obtaining a bio-based membrane with high-efficiency waterproof and breathable performance.

[0041] Example 3

[0042] Step a): Add a mixture of PU and chitosan in a mass ratio of 1:1 into a mixed solvent, stir until completely dissolved, and obtain a mixed solution; wherein the mass ratio of the mixture to the mixed solvent is 1:9. The number average molecular weight of PU is 80,000, and the number average molecular weight of chitosan is 50,000. The mixed solvent is prepared by mixing water, isopropanol and acetone in a mass ratio of 2:1:1.

[0043] Step b): The mixed solution was stirred at 60° C. for 2 hours, and then allowed to stand at room temperature for degassing for 12 hours to obtain a spinning solution.

[0044] Step c): electrospinning the spinning solution for 4 hours at a voltage of 30 kV and a receiving distance of 15 cm, changing the spinning humidity every hour to 20%, 40%, 60%, and 80%, respectively, to obtain a PU nanofiber membrane with a multi-level pore structure.

[0045] Step d): The obtained PU nanofiber membrane is heat-treated at 90°C for 30 minutes, then immersed in an ethanol solution containing diphenylmethane diisocyanate (MDI) and silane coupling agent KH-550 for 24 hours, and then heat-treated at 60°C for 30 minutes to obtain a PU nanofiber membrane with SiO2 particles grafted on the surface. The concentration of the silane coupling agent KH-550 is 5wt%, and the concentration of diphenylmethane diisocyanate is 10wt%.

[0046] Step e): Soak the PU nanofiber membrane with SiO2 particles grafted on the surface in an ethanol solution containing tetraethyl orthosilicate for 24 hours, take it out and heat-treat it at 60° C. for 30 minutes to obtain a waterproof and breathable membrane with a multi-level pore structure, wherein the concentration of tetraethyl orthosilicate is 5wt%.

[0047] Step f): vacuum drying the obtained waterproof and breathable membrane at 60° C. for 12 hours, cooling the dried waterproof and breathable membrane at a temperature of 20° C. for 30 minutes, and obtaining a bio-based membrane with high-efficiency waterproof and breathable properties.

[0048] The porosity of the bio-based membrane was determined by the liquid displacement method, and n-hexane was selected as the displacement liquid (n-hexane can easily penetrate into the fiber interior and does not cause shrinkage or expansion of the fiber structure);

[0049] The hydrostatic pressure test is carried out in accordance with the national standard GB / T4744 "Hydrostatic pressure test for water seepage resistance";

[0050] The moisture permeability test refers to the second part of GB / T 12704 "Test method for moisture permeability of textile fabrics" evaporation method to test the permeability of nanofiber membranes, including method A positive cup method and method B inverted cup method;

[0051] The washing method refers to the national standard GB / T8629 "Household washing and drying procedures for textile testing", the washing procedure is 4N, and wash 5 times.

[0052] The present invention uses the above test method to test the performance of the bio-based membranes prepared in Examples 1 to 3. The results are shown in Table 1:

[0053] Table 1 Performance test results of bio-based membranes prepared in Examples 1 to 3

[0054]

[0055] It can be seen from the above embodiments that the present invention provides a method for preparing a bio-based membrane with high-efficiency waterproof and moisture-permeable properties, comprising the following steps: a) mixing polyurethane, a polymer and a mixed solvent to obtain a mixed solution; the polymer is selected from one or more of PVA, PVA-co-PE and chitosan; b) stirring the mixed solution, standing and degassing to obtain a spinning solution; c) electrospinning the spinning solution to obtain a PU nanofiber membrane; d) using a hydrothermal-assisted sol-gel process to graft silica particles on the surface of the PU nanofiber membrane, heat-treating, soaking, taking out and continuing to heat-treat to obtain a PU nanofiber membrane with SiO2 particles grafted on the surface; e) soaking the PU nanofiber membrane with SiO2 particles grafted on the surface in an ethanol solution containing tetraethyl orthosilicate, taking out and heat-treating to obtain a waterproof and breathable membrane with a multi-level pore structure; f) drying and cooling the waterproof and breathable membrane with a multi-level pore structure to obtain a bio-based membrane with high-efficiency waterproof and moisture-permeable properties. The hydrostatic pressure of the bio-based membrane prepared by the above method decreases slightly after washing, which does not affect the overall waterproof effect; the moisture permeability does not change much, and it has high-efficiency waterproof and moisture permeability. The experimental results show that the porosity of the bio-based membrane is 91.2-93.3%; the hydrostatic pressure before washing is 104-116 kPa, and the moisture permeability of the positive cup method is 5125-5366 g / (m 2 .24h), the moisture permeability of the inverted cup method is 9560~9757g / (m 2 .24h); the hydrostatic pressure after washing is 97~112kPa, and the moisture permeability of the positive cup method is 4904~5253g / (m 2 .24h), the moisture permeability of the inverted cup method is 9378~9566g / (m 2 .24h).

[0056] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a bio-based membrane with high-efficiency waterproof and moisture permeability, comprising the following steps: a) mixing polyurethane, polymer and mixed solvent to obtain a mixed solution; the polymer is selected from one or more of PVA, PVA-co-PE and chitosan; b) stirring the mixed solution, allowing it to stand for degassing to obtain a spinning solution; c) electrospinning the spinning solution to obtain a PU nanofiber membrane; d) using a hydrothermal assisted sol-gel process to graft silica particles on the surface of the PU nanofiber membrane, heat-treating, soaking, taking out and continuing heat-treating to obtain a PU nanofiber membrane with SiO2 particles grafted on the surface; e) soaking the PU nanofiber membrane with SiO2 particles grafted on the surface in an ethanol solution containing ethyl orthosilicate, taking it out and performing heat treatment to obtain a waterproof and permeable membrane with a multi-level pore structure; f) drying and cooling the waterproof and permeable membrane with a multi-level pore structure to obtain a bio-based membrane with high-efficiency waterproof and moisture permeability.

2. The preparation method according to claim 1, characterized in that: In step a), the mass ratio of polyurethane to polymer is 1:0.8-1.2; The mixed solvent is a mixture of water, ethanol, isopropyl tone or acetone in a mass ratio of 2:0.8-1.2:0.8-1.

2.

3. The preparation method according to claim 1, characterized in that: The number average molecular weight of the polyurethane in step a) is 75000 to 85000; The number average molecular weight of PVA is 9500-11000; The number average molecular weight of PVA-co-PE is 20,000 to 77,000; The number average molecular weight of chitosan is 50,000 to 90,000.

4. The preparation method according to claim 1, characterized in that: In step b), the stirring temperature is 55-65° C. and the stirring time is 1.5-2.5 h; and the standing and degassing time is 11-13 h.

5. The preparation method according to claim 1, characterized in that: In step c), the voltage of electrospinning is 20-30 KV, and the receiving distance is 14.5-15.5 cm.

6. The preparation method according to claim 1, characterized in that: The heat treatment temperature in step d) is 85-95°C and the time is 30-60min; The temperature of continued heat treatment is 55-65°C and the time is 30-60 minutes.

7. The preparation method according to claim 6, characterized in that: The soaking liquid used in step d) comprises diisocyanate, silane coupling agent and ethanol in a mass ratio of 1:1:2; The diisocyanate is selected from toluene diisocyanate or diphenylmethane diisocyanate; The silane coupling agent is selected from KH-550 or LT-560.

8. The preparation method according to claim 1, characterized in that: The temperature of the heat treatment after taking out in step e) is 55-65° C. and the time is 30-60 min.

9. The preparation method according to claim 1, characterized in that: In step f), the drying is vacuum drying or oven drying; The vacuum drying temperature is 55-65°C and the time is 11-13h; The drying temperature is 75-85° C. and the drying time is 1-2 hours.

10. The preparation method according to claim 1, characterized in that: The cooling temperature in step f) is 15-25° C. and the cooling time is 20-40 min.

Citation Information

Patent Citations

  • Ultra-high-flux nano-fiber waterproof gas-permeable membrane and preparation method thereof

    CN107326653A

  • Preparation method of cobweb-structured blended waterproof moisture-permeable film

    CN114541040A

  • Polyurethane nanofiber waterproof moisture-permeable film as well as preparation method and application thereof

    CN117779345A

  • Moisture-permeable waterproof cloth and its production

    JP1999124774A

  • Moisture-permeable waterproof fabric and process for producing same

    WO2010126117A1

Cited By

  • Preparation method of waterproof moisture-permeable film for outdoor clothes

    CN119980570A

  • Bio-based waterproof moisture-permeable breathable film and preparation method thereof

    CN121781352A